2022
DOI: 10.5435/jaaos-d-21-00941
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Hazards in Orthopaedic Surgery Training: A Nationwide Resident Survey Involving Sharps-related Injuries

Abstract: Introduction:Surgical specialties are at an increased risk for occupational hazards, including sharps-related injuries. The objective of this study was to report the frequency of sharps injuries and evaluate which characteristics influence the number of injuries and reporting behaviors.Methods:A web-based, anonymous survey was available for 10 weeks to 46 US orthopaedic surgery residency programs (1,207 potential residents) participating in an education research collaborative. The survey was divided into the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Many of these hazards are intrinsically related to routine procedures in orthopedic surgery, including cuts and blood-borne pathogen exposure from sharps/needlestick injuries, inhalation of surgical smoke from electrocautery, noise-induced hearing loss from drills, mallets, and saws, and radiation exposure from intraoperative use of fluoroscopy. [ 1 2 3 ] Over 80% of orthopedic residents reported receiving a sharps injury during their training[ 4 ] and half of orthopedic surgeons report long-term noise-induced hearing loss as a result of their profession. [ 3 ]…”
Section: Occupational Hazards Musculoskeletal Pain and Burnout In Ort...mentioning
confidence: 99%
“…Many of these hazards are intrinsically related to routine procedures in orthopedic surgery, including cuts and blood-borne pathogen exposure from sharps/needlestick injuries, inhalation of surgical smoke from electrocautery, noise-induced hearing loss from drills, mallets, and saws, and radiation exposure from intraoperative use of fluoroscopy. [ 1 2 3 ] Over 80% of orthopedic residents reported receiving a sharps injury during their training[ 4 ] and half of orthopedic surgeons report long-term noise-induced hearing loss as a result of their profession. [ 3 ]…”
Section: Occupational Hazards Musculoskeletal Pain and Burnout In Ort...mentioning
confidence: 99%
“…Thus, even if the outer gloves were perforated, double gloving provided 98.83% protection. Another study reported that using double gloves for surgery resulted in an inner glove perforation rate of 3.7% [ 8 ]. The double gloving approach to manage glove perforation has been shown to be effective and provide greater than 90% protection for both the patient and the surgeon.…”
Section: Introductionmentioning
confidence: 99%